26‐1: Invited Paper: Metal Oxide TFT Turnkey Manufacturing Solution for a‐Si TFT Lines. Issue 1 (May 2016) - Xiao, Tian; Yu, Gang; Shieh, Chan‐Long; Park, Jung‐Woo; Foong, Fatt; Lee, Karman; Musolf, Juergen; Wang, Guangming; Ottoson, Kristoffer; Yang, Kaixia; Wang, Jeff; Berkoff, Bruce; et al.
Abstract : There is strong incentive to upgrade a‐Si TFT lines with minimal investments to enable high‐end display manufacturing. We developed an oxide TFT manufacturing process which keeps the high‐throughout SiNx GI and wet BCE process used in a‐Si TFT lines, enabling high resolution LCD and OLED display manufacturing with minimal equipment upgrade and production costs.